Densitas tulang alveolar pada penderita periodontitis kronis dan periodontitis agresif melalui radiografi - Rahmania Rahmania; Lusi Epsilawati; Nunung Rusminah (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: The purpose of this study was to determine alveolar bone density in patients with chronic periodontitis and aggressive periodontitis through panoramic radiography . Material and Methods: The method used in this study was descriptive. This study was conducted on populations that met all criteria. The sampling method used was purposive sampling technique, so that 31 panoramic radiographs were diagnosed with chronic periodontitis and 7 panoramic radiographs were diagnosed with aggressive periodontitis. Results: The study showed that bone density in chronic periodontitis had an average of bony trabeculae 28.6% and marrow spaces 71.4% while bone density in aggressive periodontitis had an average bony trabeculae 20.2% and marrow spaces 79.8% Conclusion: Based on the results of the study it can be concluded that bone density in patients with chronic periodontitis and aggressive periodontitis has a low bone density value. The average bone density in patients with chronic periodontitis and aggressive periodontitis has different values, where the bone density in chronic periodontitis is greater than aggressive periodontitis.